2019
DOI: 10.6023/cjoc201903069
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Sulfur-Containing Perfume & Flavors Construction

Abstract: Scientists have found more and more sulfur compounds in food with the development of science and technology, high-precision analytical methods and equipment. In 2015, Flavor and Extract Manufactures Association of the United State published 2816 safe flavors, and there are more than 388 sulfur-containing compounds, accounting for more than 13%. The main smell of sulfur-containing flavors is food, especially the non-staple food and dishes. It is mainly used as food flavor, flower flavor and fruity flavor. Due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Organosulfur chemistry has attracted more and more attention and brought increasing significance because carbon–sulfur bonds widely exist in nature, including biologically active molecules 1 – 4 , pharmaceuticals 5 , agrochemicals 6 , materials 7 , flavors, and fragrances 8 , and even food ingredients 9 . Sulfur-containing motifs frequently play a vital role in organic photoelectric materials and biologically active compounds because S atom possesses strong polarizability and hyperpolarizability.…”
Section: Introductionmentioning
confidence: 99%
“…Organosulfur chemistry has attracted more and more attention and brought increasing significance because carbon–sulfur bonds widely exist in nature, including biologically active molecules 1 – 4 , pharmaceuticals 5 , agrochemicals 6 , materials 7 , flavors, and fragrances 8 , and even food ingredients 9 . Sulfur-containing motifs frequently play a vital role in organic photoelectric materials and biologically active compounds because S atom possesses strong polarizability and hyperpolarizability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 2-methyl-3-furyl sulfide spice compounds are also important fine chemical raw materials and organic synthesis intermediates, which are widely used in food, chemicals, pharmaceuticals, and agriculture. 14 In recent years, some studies have shown that 2-methyl-3-furyl sulfide spice compounds possess a variety of biological functions, including anticancer and antibacterial properties ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number and variety of sulfur-containing spice compounds are still increasing. Sulfur-containing spice compounds generally elicit a response at small dosages and are present in food-related aromas such as meats, seafood, coffee, onion, garlic, leek, cabbage, and tropical fruits. Therefore, sulfur-containing spice compounds are widely used in the preparation of food and various flavors …”
Section: Introductionmentioning
confidence: 99%
“…6−9 Therefore, sulfurcontaining spice compounds are widely used in the preparation of food and various flavors. 6 Sulfur-containing spice compounds have many biological and functional properties, and thus they are widely used in the food, chemical, agriculture, material, and medicine industries. In recent years, a large number of studies have shown that sulfur-containing spice compounds possess a variety of biological functions (Figure 1), including antioxidant, antiinflammatory, antiobesity, anticancer, insecticidal, and nematicidal properties.…”
Section: Introductionmentioning
confidence: 99%